Educational Tourism: Adoption of Art Management Technologies in the Activity of Universities - KOMANDYSHKO, Elena F.; SEMENOVA, Elena A. (Journal of Environmental Management and Tourism; Vol 8 No 6 (2017): JEMT Volum VIII Issue 6(22) Fall 2017, 2018)
The authors of this paper consider the problem of organization of educational tourism for students in the context of adoption of art management innovative technologies. The paper deals with the functional interaction between management and educational tourism that helps to reveal the prospects for reducing art management technologies to practice of educational institutions at the current stage. The authors reveal the specifics and peculiarities of educational tourism in formation of students’ abilities of using the methodology of regional routes as an example. The Village Theater, a methodology for developing a regional route, is presented with the purpose of preparing and implementing shows, concerts and theatrical performances. The paper shows that the targets for application of art management technologies in the sphere of educational tourism are aimed at expanding the subject content, combining various forms of professional activity, providing students with conditions for personal self-development and their own tries in their professional activities.